2005
DOI: 10.1007/s10565-005-0166-6
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial perturbation attenuates bile acid-induced cytotoxicity

Abstract: Hydrophobic bile acids such as deoxycholate (DOC) are known to damage liver cells during cholestasis and promote colon cancer. Cellular stresses induced by bile acids, which include mitochondrial and endoplasmic reticulum (ER) stresses, can result in apoptosis. We found that inhibition of mitochondrial complexes I-V with rotenone, thenoyltrifluoroacetone (TTFA), antimycin A, myxothiazol or oligomycin strongly protected against DOC-induced apoptosis of HCT-116 cells. To understand the mechanism of this protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 103 publications
2
18
0
Order By: Relevance
“…Since previous works have reported that BA can disrupt intracellular organelles (mitochondria, or Golgi) [4,29,31], we first analysed the structure of the cell compartments of human colonic epithelial cells following 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 incubation with BA. Transmission electron microscopy (TEM) revealed that administration of low concentrations of CDC (0.1mM or 0.3mM) for 1-10 min had no effect on the structure of intracellular organelles (Fig.…”
Section: High Concentration Of Bile Acid Induces Severe Mitochondrialmentioning
confidence: 99%
“…Since previous works have reported that BA can disrupt intracellular organelles (mitochondria, or Golgi) [4,29,31], we first analysed the structure of the cell compartments of human colonic epithelial cells following 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 incubation with BA. Transmission electron microscopy (TEM) revealed that administration of low concentrations of CDC (0.1mM or 0.3mM) for 1-10 min had no effect on the structure of intracellular organelles (Fig.…”
Section: High Concentration Of Bile Acid Induces Severe Mitochondrialmentioning
confidence: 99%
“…When cells of human colonic origin (HCT116) were treated with the bile acid deoxycholate (0.5 mmol/L) for 4 h, the majority of cells entered apoptosis. However pretreatment of the cells with sodium azide, which binds to CcO and inhibits the protein complex from functioning, significantly reduced the fraction of cells undergoing apoptosis upon further treatment with deoxycholate [22] , indicating that CcO deficient cells are resistant to induction of apoptosis. We previously showed that reduction in CcOI expression correlated with a reduction in apoptotic competence in nearby tissue samples from the same colonic epithelium [6] .…”
Section: A Hypothetical Sequence Of Events In Progression From a Defementioning
confidence: 99%
“…5 Patients taking proton pump inhibitors have a significantly higher incidence of overgrowth of gastric bacteria and, consequently, increased concentrations of unconjugated bile acids, including DCA. 10 Bile acids induce mitochondrial alterations, [11][12][13] oxidative stress 11 12 14 15 and DNA damage. [14][15][16] We have also shown that perturbation of mitochondria can lead to apoptosis resistance.…”
mentioning
confidence: 99%